Despite doubt : embracing a confident faith - Wittmer, Michael Eugene (2013)
"Many Christians struggle with the concept of walking by faith, especially in a world that says faith is all about taking risks-leaping into uncharted territory and expecting everything to be okay. In Despite Doubt, Michael E. Wittmer reexamines this popular viewpoint and encourages readers to get a clear understanding of their assurance in God and salvation. Readers will examine the flip side of doubt that opens the door to questions, answers, and knowledge about securing their trust in God. Helping readers to discover how to embrace a confident faith, Despite Doubt includes questions for reflection and discussion and is a perfect resource for small group study"--
"Feeding the Soul with the Word of God"
Includes bibliographical references (pages 181-187).
Keywords: Faith; Christian life; RELIGION / Christian Life / General